Analisis Laporan Keuangan Dalam Mengukur Kinerja Keuangan Pada Perusahaan Tambang Batu Bara Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2022 - Maryanto, Maryanto; Sarmigi, Elex; Kusmila, Zesmi; Wahyuni, Endah Sri (JURNAL ONLINE INSAN AKUNTAN; Vol 9 No 1 (2024): Jurnal Online Insan Akuntan (Juni 2024), 2024)
The recent industrial growth in Indonesia has shown a positive trend with advanced innovations and significant expansion in the Islamic banking sector. However, the mining industry has experienced a decline, posing unique challenges. Despite Indonesia's abundant natural resources, the mining sector, particularly coal, faces significant fluctuations in global prices, impacting the performance of coal mining companies on the Indonesia Stock Exchange (IDX). This analysis employs Economic Value Added (EVA) and Market Value Added (MVA) as indicators of the financial performance of coal mining companies.The results reveal that some companies have successfully created positive value addition, but the overall sector undergoes significant fluctuations. These fluctuations are largely influenced by the volatility of coal prices in the global market. During certain periods, a decrease in coal prices leads to a decline in pre-tax profit and the value addition of companies. On the other hand, price increases in other periods have a positive impact. Despite some companies managing these risks, MVA analysis indicates that shareholder welfare is still affected by market fluctuations.